#TITLE_ALTERNATIVE# - AZIZAH KUSUMANINGRUM (NIM: 12405019), NURUL
This study tried to explain how the occurrence of main earthquake could influence the static stress change in its neighborhood that may trigger aftershock or subsequent events. Using Coulomb failure criterion, we tried to obtain model of dynamic stress in the Sumatra subduction zone that altering in response to Aceh earthquake on December, 2004. We found the interrelated between static stress change and subsequent events. Nias earthquake occurred in rupture zone where static stress raised by two bars post-seismic Aceh Earthquake. Both Aceh and Nias earthquakes raised the stress along south Sumatra subduction fault by 1,5 Ã‚Â– 2 bars triggering Bengkulu earthquake in 2007. Following the pattern of static stress transfer that occurred after Aceh to Bengkulu earthquake, we estimated the hazardous regions where the next earthquakes might be occurred. That is alongside of Mentawai Islands